Assessment of Rock Slope Stability along Sulaimaniyah -Qaradagh Main Road, Near Dararash Village, Sulaimaniyah, NE-Iraq - Hamasur, Ghafor A.; Mohammed, Fahmy O.; Ahmad, Ashna J. (Iraqi Journal of Science, 2020)
The road network in the Baranan mountain, near Dararash village, connecting Sulaymaniyah city with Qaradagh town, plays a major role in socio- economic activities of Qaradagh town and its surrounding villages. Any type of slope failure in the area may cause breaking up in traffic, loss of lives, and injuries. For assessing the stability of rock slopes in the area, seven stations (rock-cut slopes) were selected along the road and evaluated by kinematic analysis, using DIPS v6.008 software and slope mass rating system (SMRTool - v205 software). The kinematic analysis revealed that planar and wedge sliding may occur in stations no.2, 5, 6, and 7, flexural toppling may occur in station no.1, direct toppling may occur in station no.2, and oblique toppling may occur in station no.3. SMR- Tool software for discrete-SMR and continuous-SMR (CSMR) revealed that stations no.2, 5, 6 and 7 are unstable slopes (class IV of a bad slope type) with failure probability of 0.6, with an exception for station no.7 which is a partially stable slope (class III of a normal slope type) with failure probability of 0.4. Station no.1 is partially stable slope (class III of a normal slope type) with failure probability of 0.4 and station no.3 is stable slope (class II of a good slope type) with failure probability of 0.2. Due to the lack of structural and failure surface data (attitude of discontinuities and slumping surface) in station no.4, stability analysis was interpreted by using the general conventional method, depending on the field criterion and vision. The station can be interpreted as a rotational failure, the upper part of which consists of slump motion and the lower part of flow motion.